2008
DOI: 10.1371/journal.pone.0003455
|View full text |Cite
|
Sign up to set email alerts
|

Incompetence of Neutrophils to Invasive Group A streptococcus Is Attributed to Induction of Plural Virulence Factors by Dysfunction of a Regulator

Abstract: Group A streptococcus (GAS) causes variety of diseases ranging from common pharyngitis to life-threatening severe invasive diseases, including necrotizing fasciitis and streptococcal toxic shock-like syndrome. The characteristic of invasive GAS infections has been thought to attribute to genetic changes in bacteria, however, no clear evidence has shown due to lack of an intriguingly study using serotype-matched isolates from clinical severe invasive GAS infections. In addition, rare outbreaks of invasive infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
79
0
6

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 44 publications
2
79
0
6
Order By: Relevance
“…Activated PMNs can phagocytose and kill GAS (37). Similarly, impaired PMN function, due to failure of PMN migration following CXC chemokine destruction or due to necrosis of PMNs by the pore-forming toxin streptolysin O, results in severe GAS infection (32). In this study, we observed that the efficacy of J8-DT vaccination was ablated in PMN-depleted mice.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Activated PMNs can phagocytose and kill GAS (37). Similarly, impaired PMN function, due to failure of PMN migration following CXC chemokine destruction or due to necrosis of PMNs by the pore-forming toxin streptolysin O, results in severe GAS infection (32). In this study, we observed that the efficacy of J8-DT vaccination was ablated in PMN-depleted mice.…”
Section: Discussionmentioning
confidence: 54%
“…Accessory immune cells are known to play a critical role in protection against streptococci (24,31,32). We show that skin-resident macrophages contribute to the control of bacterial burden in the skin, whereas systemic macrophages contribute to the control of systemic infection.…”
Section: Role Of Macrophages In J8-dt-mediated Early Immunitymentioning
confidence: 76%
“…3B, it is seen that genes derepressed in M23ND/CovS Ϫ , viz., hasABC, slo and nga, the mga regulon, spyA, and prtS, are highly associated with invasiveness and antiphagocytosis, which are important for deeper colonization and resistance to neutrophil killing of GAS. Previous studies also showed that these genes have higher expression in invasive GAS infections than in noninvasive infections (3,5,47), and expression of the genes is considered essential for evasion, persistence, and/or dissemination (48)(49)(50). Remarkably, the highly elevated expression of the hasABC operon played a key role in resistance to host killing in invasive infections of GAS.…”
Section: Validation Of Regulated Virulence Genes By Q-rt-pcrmentioning
confidence: 95%
“…Hypervirulent S. pyogenes of the emm1 genotype has recently been associated with more severe invasive diseases (3). According to previous investigations (2)(3)(4)(5), emm1 hypervirulent S. pyogenes is defined by the abundant production of numerous virulence factors such as the superantigen, streptococcal exotoxin A (SpeA), the nuclease, streptococcal DNase (Sda1), the cytotoxin nicotinamide adenine dinucleotide (NAD)-glycohydrolase (NADase), and the hemolysin streptolysin O (SLO), but not the proteinase streptococcal exotoxin B (SpeB). The phenotype is mostly explained by mutations in the covR/S genes that comprise a two-component signal transduction system that affects the expression of up to 15z of S. pyogenes genes, including many expressing virulence factors (4).…”
mentioning
confidence: 98%
“…S. pyogenes commonly causes pharyngitis among schoolchildren, as well as invasive diseases such as sepsis and streptococcal toxic shock syndrome (STSS), which have become more prevalent globally during the last 25 years. STSS is associated with symptoms of hypotension, renal impairment, disseminated intravascular coagulopathy, liver involvement, adult respiratory distress syndrome, generalized erythematous macular rash, soft tissue necrosis, and central nervous disorders, and mortality rates range from 30z to 70z (1,2). Hypervirulent S. pyogenes of the emm1 genotype has recently been associated with more severe invasive diseases (3).…”
mentioning
confidence: 99%